SPATIO-TEMPORAL CHARACTERISTICS OF SEA LEVEL ANOMALY IN THE INDONESIAN WATER - Sarsito, Dina Anggreni; Wijaya, Dudy Darmawan; Trihantoro, Nur Fajar; Fathulhuda, Muhammad Syahrullah; Pradipta, Dhota (GEOMATIKA, 2019)
Indonesia is an archipelago state lies between Indian and Pacific Oceans at the South East Asia region. Its unique geomorphological and geographical setting affect variabilities of instantaneous sea surface height (ISSH) concering to one of the sea reference surface i.e mean sea surface height (MSSH). The differences between both heights, known as sea level anomaly (SLA), can be recognized as one of the parameter that describes the dynamic phenomena of the ocean. We investigated the Spatiotemporal characteristics of long-term SLA in this research based on 30 years of sea-level data derived from the multi-mission of satellite Altimetry (Topex/Poseidon, Jason-1, Jason-2 and Jason-3). The Spatiotemporal of SLA characteristics in Indonesian waters indicate substantial variations due to the influences of geographical location, bathymetric depth, and seasonal patterns. The SLA rate in the Indonesian region provides values that vary between 3.4 mm/yr to 5.3 mm/yr that higher than 3.2 mm/yr global SLA rate. The impact caused by the phenomenon needs to be taken into account given the vulnerability and disaster that could endanger the islands and coastal area in Indonesia.